Analisis Hukum Peningkatan Tarif Nilai Objek Pajak Tidak Kena Pajak dalam Transaksi Jual Beli Tanah di Kabupaten Jember - Anggriani, Alvi; Ruslan, Achmad; Arisaputra, Muhammad Ilham (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2023)
This study aims to analyze the policy of imposing acquisition value of tax objects is not taxable (NPOPTKP) tariff increases in land buying and selling transactions and the authority of the Jember district government in determining the increase in NPOPTKP rates in Jember district. This research was conducted using empirical research methods. The results of this study indicate (1) the policy of imposing an increase in tariffs of NPOPTKP in land sale and purchase transactions in Jember Regency has been regulated following with applicable laws and following with existing regional regulations, namely following with Jember Regent Regulation Number 45 of 2021 concerning Amendments to Regent Regulation Number 38 of 2011 concerning Procedures for Collection of Fees for Acquisition of Land and Building Rights; (2) The authority of the regional government of Jember Regency in determining the increase in tariffs on the value of non-taxable tax objects has been implemented by Law Number 28 of 2009 concerning Regional Taxes and regional levies to expand regional tax objects and regional levies and to provide discretion in determining the rates to the local government considering that it is necessary to increase the tariffs of NPOPTKP in land buying and selling transactions caused by a discrepancy between the realization of tax revenues and the targets set due to non-compliance by the public in carrying out their tax obligations. The application of administrative sanctions for taxpayers who do not comply in carrying out their tax obligations should be implemented by the Regional Planning and Revenue Agency (Bappeda) so that the target of revenue in the tax sector that has been set can be achieved to the maximum.